2014
DOI: 10.1177/0973408214548369
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the GAP: Ideas for the UNESCO Post-2014 ESD Agenda

Abstract: This paper explores how ESD activities may be viewed on a continuum from 'causal' approaches, seeking to cause change in others, to 'enabling' orientations where efforts are made to enable people to implement the principles of ESD and respond to the environmental challenges they face from their own context. An enabling orientation seeks to both 'mobilise' participant's perspectives and engage with them in a systems-wide or holistic space. They tend to make more meaning for learners by making useful connections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…These ideas and concepts form the basis of this paper which advocates an 'enabling' orientationrather than a traditional 'causal' approach (i.e. seeking to cause a change in others through top-down methodologies) (Taylor, 2014).…”
Section: Stakeholder Participation Through Citizen Sciencementioning
confidence: 99%
“…These ideas and concepts form the basis of this paper which advocates an 'enabling' orientationrather than a traditional 'causal' approach (i.e. seeking to cause a change in others through top-down methodologies) (Taylor, 2014).…”
Section: Stakeholder Participation Through Citizen Sciencementioning
confidence: 99%
“…This prevailing assumption endures despite research and experience showing that there is no causal relationship between attitudes and behaviour (Kemmis & Mutton, 2012). We have found that change-choice-practices, where participants are encouraged to make choices for a sustainable future, enable change in more powerful ways (Taylor, 2010, 2014). This approach to change draws on ‘nudge’ research and is gaining momentum.…”
Section: Innovations For Our Timesmentioning
confidence: 99%
“…Teachers are important actors that can effectively integrate sustainability competencies. Presently, they reportedly face challenges in making useful connections between theory and context-relevant practice, thus disabling application of ESD principles to new contexts (Taylor, 2014;Pace, 2010). Despite efforts for its mainstreaming, teachers resist by complaining of overload and believing that ESD is an externally imposed constraint (Gokool-Ramdoo, 2012).…”
Section: Esd Leadership and Coordination: Capacity Deficienciesmentioning
confidence: 99%